Design of Optimal Control Model for Cascade Hydro Power Plants - Babunski, Darko; Spasovski, Sasho; Tuneski, Atanasko; Zaev, Emil (SAVEZ ENERGETIČARA SRBIJE, 2020)
Hydro energy represents big challenge in development of the whole society. Hydro energy plants are environment friendly, without big influence to the water, air and soil. Additionally, dams are providing benefits in form of flood control, water distribution systems for drinking and agriculture purposes. Hydro energy obtained from Hydro Power Plants (HPP) is very flexible in relation to fast changes in Energy system, with very fast starting time which make energy system more stable and secure, with higher efficiency. In this paper analysis of the optimal exploitation of the cascade HPPs, with hydraulically connected water reservoirs is made. Used optimization technique leads to design of optimal control for cascade HPPs, according to higher efficiency coefficient related to production of most energy with optimal water flow thru turbines of the HPPs, without affecting the environment.
Projektovanje modela optimalnog upravljanja sa kaskadno povezanim hidroelektranama
Keywords: Hydro Power Plant, Hydro Turbine, Optimal control, cascade systems